Vanadium-based electrode material, preparation method of vanadium-based electrode material, positive pole piece, battery and electric device
By loading the in-situ FeVO4 thin sheet structure on a carbon-containing substrate, the problems of limited resources and safety hazards of lithium-ion batteries are solved, the cycle stability and rate performance of zinc-ion batteries are improved, and efficient electrochemistry is achieved Performance and easy preparation process.
Patent Information
- Application Number
- CN202411264839.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-17
AI Technical Summary
Lithium-ion batteries have limited lithium resources, high production costs, and toxic and flammable electrolytes, which limit their further applications, and their cycle life and rate performance are insufficient, making it difficult to meet the needs of large-scale energy storage equipment.
The vanadium-based electrode material is used, including a thin flower-like structure of FeVO4 loaded in situ on a carbon-containing substrate, and is prepared by soaking soluble iron salt and vanadium salt solution for heating and calcining to improve electrochemical performance and stability.
It improves the cycle stability, rate performance and specific capacity of zinc ion batteries, reduces production costs, simplifies the preparation process, enhances the conductivity and mechanical properties, and avoids the resistance brought by the adhesive.
Smart Images

Figure CN119153648A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and in particular to a vanadium-based electrode material and a preparation method thereof, as well as a positive electrode sheet, a battery and an electrical device. Background Art
[0002] The rapid consumption of fossil fuels and the use of non-renewable energy sources have caused serious pollution to the environment. In order to respond to green and sustainable development and reduce environmental pollution, environmentally friendly lithium-ion batteries, energy storage systems and hydrogen energy have been booming. At present, lithium-ion batteries are widely used in consumer electronics and electric vehicles due to their advantages such as high energy density, high voltage platform, no memory effect, and long cycle life. However, the limited and uneven distribution of lithium resources on the earth have raised production costs, and the safety hazards caused by toxic and flammable electrolytes have limited the further application of lithium-ion batteries. In recent years, researchers have begun to turn their attention to rechargeable multivalent metal ions (such as Al 3+ Mg 2+ , Ca 2+ and Zn 2+ It is believed that lithium-ion batteries have the potential to replace lithium-ion batteries in large-scale energy storage devices.
[0003] Among various multivalent metal ion battery systems, zinc ion batteries have attracted particular attention, mainly for the following reasons: zinc ion batteries usually use aqueous electrolytes, which are non-flammable and usually non-toxic, safer and environmentally friendly; the application of aqueous electrolytes has relatively loose requirements on production equipment and production environment, reducing manufacturing costs; zinc has relatively high energy density, power density and theoretical specific capacity; zinc is abundant on the earth and is easy to obtain and cheap, further reducing the production cost of batteries. Based on the above reasons, it can well make up for the shortcomings of traditional lithium ion batteries.
[0004] At present, the mainstream research directions of zinc-ion battery cathode materials are mainly manganese-based, vanadium-based, and Prussian blue analogs. Among them, vanadium-based materials have relatively high specific capacity, low production cost and simple synthesis, which makes them have an advantage in the competition with other cathode materials. Summary of the invention
[0005] In view of this, the purpose of the present application is to provide a vanadium-based electrode material and a preparation method thereof, so that the vanadium-based electrode material can improve the electrochemical performance of the battery, including cycle performance, rate performance, stability, capacity, etc.;
[0006] Another object of the present application is to provide a positive electrode sheet, a zinc ion battery and an electrical device based on the above-mentioned vanadium-based electrode material.
[0007] In order to solve the above technical problems / achieve the above purposes or at least partially solve the above technical problems / achieve the above purposes, as a first aspect of the present application, a vanadium-based electrode material is provided, comprising a carbon-containing substrate and FeVO4; the FeVO4 has a flower-like structure composed of thin flakes and is in-situ loaded on the carbon-containing substrate.
[0008] Optionally, the carbon-containing substrate comprises carbon cloth.
[0009] As a second aspect of the present application, a method for preparing the vanadium-based electrode material is provided, comprising:
[0010] The carbon-containing substrate is immersed in a solution containing a soluble iron salt and a soluble vanadium salt, and after heating for reaction, the carbon-containing substrate is taken out and dried;
[0011] The dried carbon-containing substrate is calcined to obtain the vanadium-based electrode material.
[0012] Optionally, the soluble iron salt includes one or more of ferric chloride, ferric nitrate, and ferric sulfate; the soluble vanadium salt includes one or more of ammonium metavanadate and vanadyl acetylacetonate.
[0013] Optionally, the temperature of the heating reaction is 50-200°C.
[0014] Optionally, the calcination temperature is 300-700°C.
[0015] Optionally, the method further comprises pre-treating the carbon-containing substrate to be hydrophilic and remove a surface oxide layer before immersion.
[0016] As a third aspect of the present application, a positive electrode plate is provided, comprising the vanadium-based electrode material described in the present application.
[0017] As a fourth aspect of the present application, a battery is provided, comprising a negative electrode plate, a separator, an electrolyte, and the positive electrode plate described in the present application.
[0018] As a fifth aspect of the present application, an electrical device is provided, which includes the battery described in the present application.
[0019] The present application in-situ loads a flower-like structure composed of FeVO4 flakes on a carbon-containing substrate. This composite structure avoids the resistance caused by the use of a binder, is more conducive to electron transmission and improves conductivity; the FeVO4 material is attached to a carbon-containing substrate with a large specific surface area, combined with its own flower-like nano-space structure, so that the material can be in contact with the electrolyte to fully contact and infiltrate, thereby increasing the diffusion and deintercalation rate of conductive active ions, improving the rate performance and cycle stability, so that when used as an electrode in the positive electrode of a battery, it exhibits a higher specific capacity and excellent cycle stability. At the same time, the preparation method of the vanadium-based electrode material described in the present application is also more efficient and simple. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application.
[0021] Figure 1 Shown is a SEM image of the vanadium-based electrode material of the present application;
[0022] Figure 2 Shown is a SEM image of the flower-like structure of FeVO4 thin sheets in the vanadium-based electrode material of the present application;
[0023] Figure 3 Shown is a schematic diagram of preparing the vanadium-based electrode material of the present application;
[0024] Figure 4 The figure shows the SEM image of the FeVO4 material without carbon cloth in the comparative example; the arrow in the figure points to the granular FeVO4 material;
[0025] Figure 5 Shown is a graph of the cycle performance of a zinc ion battery using the vanadium-based electrode material of the present application and the carbon-free FeVO4 material of the comparative example as the positive electrode at a current density of 0.1 A / g. DETAILED DESCRIPTION
[0026] The present application discloses a vanadium-based electrode material and a preparation method thereof, as well as a positive electrode sheet, a battery and an electrical device. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all deemed to be included in this application. The products, processes and applications described in this application have been described through preferred embodiments. Relevant personnel can obviously modify or appropriately change and combine the products, processes and applications described in this article without departing from the content, spirit and scope of this application to realize and apply the technology of this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0027] It should be noted that, in this article, if relational terms such as "first" and "second", "step 1" and "step 2", and "(1)" and "(2)" appear, they are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "comprise", "include" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or equipment including the elements. At the same time, the embodiments in this application and the features in the embodiments may be combined with each other without conflict.
[0028] In the first aspect of the present application, a vanadium-based electrode material is provided, including a carbon-containing substrate and FeVO4; the FeVO4 has a flower-like structure composed of thin sheets and is in-situ loaded on the carbon-containing substrate. The FeVO4 material synthesized in the present application has a unique flower-like spatial structure formed by many thin sheets in microscopic morphology, which makes the specific surface area larger and fully contacts with the electrolyte, further improves the diffusion and deintercalation rate of zinc ions, improves the rate performance and cycle stability, and the SEM image of the material is shown in FIG. Figure 1 and Figure 2 .
[0029] In certain embodiments of the present application, the carbon-containing substrate includes carbon cloth. Carbon cloth has a high specific surface area and electrical conductivity, as well as good mechanical properties. By directly growing flower-shaped FeVO4 in situ on the carbon cloth, the electrode material can obtain better electrochemical and mechanical properties using the carbon cloth, and the obtained self-supporting structure can reduce the use of binders, eliminate the resistance caused by the binder, and the conductivity of the material is better.
[0030] In a second aspect of the present application, a method for preparing the vanadium-based electrode material is provided, comprising:
[0031] The carbon-containing substrate is immersed in a solution containing a soluble iron salt and a soluble vanadium salt, and after heating for reaction, the carbon-containing substrate is taken out and dried;
[0032] The dried carbon-containing substrate is calcined to obtain the vanadium-based electrode material.
[0033] In certain embodiments of the present application, the soluble iron salt and the soluble vanadium salt are added according to the element molar ratio of FeVO4, that is, Fe:V=1:1. The soluble iron salt includes one or more of ferric chloride, ferric nitrate, and ferric sulfate; the soluble vanadium salt includes one or more of ammonium metavanadate and vanadium acetylacetonate. The solution can be dissolved in water or ethanol.
[0034] In some other embodiments of the present application, a hydrothermal kettle with a polytetrafluoroethylene liner is used as a reaction container, and the carbon cloth is immersed in a mixed solution of a soluble iron salt and a soluble vanadium salt, and the mixture is sealed and heated for reaction.
[0035] In certain embodiments of the present application, the temperature of the heating reaction is 50-200° C., and the reaction time is 1-5 hours; for example, the reaction is carried out at 150° C. for 2 hours.
[0036] In certain embodiments of the present application, the calcination temperature is 300-700° C., and the calcination time is 1-5 h, for example, calcination at 500° C. for 2 h.
[0037] In certain embodiments of the present application, the carbon-containing substrate is also subjected to pretreatment for hydrophilization and removal of the surface oxide layer before immersion. The hydrophilization treatment includes, but is not limited to, chemical methods, physical methods, or a combination of the two. In the present application, a mixed acid formed by concentrated nitric acid and concentrated sulfuric acid is used to hydrophilize the carbon-containing substrate. The treatment process can be assisted by heating, for example, 60-90°C for 1-5h, and the volume ratio of concentrated nitric acid to concentrated sulfuric acid can be selected as 3:1. The surface oxide layer removal treatment is carried out by ultrasonic treatment after immersion in ethanol and water.
[0038] In the third aspect of the present application, a positive electrode sheet is provided, comprising the vanadium-based electrode material described in the present application. The vanadium-based electrode material described in the present application can be directly used as a positive electrode sheet, or can be prepared into a positive electrode sheet in combination with other components or materials, and these components or materials can be added to increase certain electrochemical properties of the battery.
[0039] In the fourth aspect of the present application, a battery is provided, comprising a negative electrode sheet, a separator, an electrolyte, and the positive electrode sheet described in the present application. More specifically, a zinc-ion battery battery comprising the positive electrode sheet described in the present application, wherein the zinc-lithium-ion battery includes but is not limited to a soft-pack battery, a button battery, a square-shell battery, a half-battery or a full battery, etc.
[0040] In certain embodiments of the present application, the zinc ion battery is a button cell, comprising a negative electrode shell, a spring, a gasket, a negative electrode sheet (zinc sheet), an electrolyte, a diaphragm, a positive electrode sheet (vanadium-based electrode material of the present application) and a positive electrode shell. The diaphragm is glass fiber, and the electrolyte is a 2M aqueous solution of ZnSO4.
[0041] In a fourth aspect of the present application, an electric device is provided, comprising the battery described in the present application, wherein the battery provides electric energy for the electric device. The electric device may be various devices or equipment driven by the lithium-ion battery, including but not limited to electric vehicles, electric vehicles, self-balancing vehicles, flatbed vehicles, aircraft, lighting equipment, household appliances, etc.
[0042] In each group of comparative experiments provided in this application, unless otherwise specified, other experimental conditions, materials, etc. are kept consistent except for the differences indicated in each group, so as to provide comparability. The experimental materials and reagents used in the examples can be obtained from commercial channels unless otherwise specified.
[0043] The following is a further description of a vanadium-based electrode material and a preparation method thereof, as well as a positive electrode sheet, a battery and an electrical device provided in the present application.
[0044] Embodiment 1:
[0045] Step 1: Carbon cloth pretreatment. Place a 20mm*50mm carbon cloth in a mixed solution of concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 3:1, heat to 80℃ and keep for 3h for hydrophilization treatment, then soak it in ethanol and deionized water in turn and ultrasonically treat it for 10min respectively to remove the surface oxide layer, and finally vacuum dry the treated carbon cloth at 60℃ for use.
[0046] Step 2: Weigh 0.487g FeCl3 and 0.351g NH4VO3, add 30mL deionized water and stir for 15min to fully dissolve and mix. Transfer the solution to a 50mL polytetrafluoroethylene-lined hydrothermal reactor and add the carbon cloth (such as Figure 3 As shown), seal it and heat it to 150°C for 2h. After the reaction, take out the carbon cloth, wash it with deionized water and dry it.
[0047] Step 3: Place the dried carbon obtained after the reaction in step 2 in a muffle furnace and calcine at 500° C. for 2 hours in an air atmosphere to obtain a FeVO4 / carbon cloth electrode material.
[0048] Figure 1 Shown is the SEM of the obtained material, showing a large amount of flower-like FeVO4 grown on the carbon cloth. Figure 2 shows the details of the FeVO4 flower-like nanostructure attached to the carbon cloth.
[0049] Comparative Example 1:
[0050] Step 1: Weigh 0.487g FeCl3 and 0.351g NH4VO3, add 30mL deionized water and stir for 15min to fully dissolve and mix. Transfer the solution to a 50mL polytetrafluoroethylene-lined hydrothermal autoclave, seal it and heat it to 150℃ for 2h. Collect the yellow solid after the reaction, wash it with deionized water and dry it.
[0051] Step 2: Place the dried solid obtained after the reaction in step 1 in a muffle furnace and calcine at 500° C. for 2 hours in an air atmosphere to obtain FeVO4.
[0052] Figure 4 This is the SEM of the material obtained by the reaction without carbon cloth. It can be seen that there are fewer FeVO4 flower-like nanostructures generated without the attachment of carbon cloth, and a considerable number of large granular FeVO4 appear. The introduction of carbon cloth in the present application can promote the transformation of FeVO4 into flower-like nanostructures, thereby promoting the electrochemical performance of the battery.
[0053] Experimental example:
[0054] 1. Battery assembly
[0055] Example 1: FeVO4 / carbon cloth material itself can be used as the positive electrode. The prepared FeVO4 / carbon cloth is cut into discs with a diameter of 12 mm and used as the positive electrode of button batteries. Note that after the above step 1, discs of the same size should be cut and weighed as the mass of the carbon cloth to calculate the mass of the active substance.
[0056] Button cells were made to test the electrical properties of the materials. The prepared electrode was used as the positive electrode of the battery, the cleaned and dried zinc sheet with a diameter of 14 mm was used as the negative electrode, the glass fiber was used as the battery separator, and a 2M ZnSO4 aqueous solution was used as the electrolyte. The assembly order was: negative electrode shell, spring, gasket, negative electrode sheet (zinc sheet), dripping electrolyte, separator, dripping electrolyte again, positive electrode sheet (FeVO4 / carbon cloth), positive electrode shell, and then placed on a tablet press to complete the button battery production.
[0057] Comparative Example 1: Active material (prepared FeVO4), conductive agent (conductive carbon black) and binder (PVDF) were fully mixed, ground and dispersed in NMP at a mass ratio of 7:2:1 to prepare slurry. The slurry was then coated as evenly as possible on a stainless steel mesh with a diameter of 12 mm that was accurately weighed in advance. After coating, it was placed in a vacuum drying oven at 60°C and dried until the NMP in the slurry was completely volatilized to obtain a positive electrode sheet.
[0058] Then, a button cell was made in the manner of Example 1 to test the electrical properties of the material, with the prepared electrode as the positive electrode of the battery, a cleaned and dried zinc sheet with a diameter of 14 mm as the negative electrode, glass fiber as the battery separator, and a 2M ZnSO4 aqueous solution as the electrolyte; the assembly order was: negative electrode shell, spring sheet, gasket, negative electrode sheet (zinc sheet), dripping electrolyte, separator, dripping electrolyte again, positive electrode sheet (FeVO4), positive electrode shell, and then placed on a tablet press and pressed to complete the button cell production.
[0059] 2. Cycle performance test
[0060] The voltage range used in the test is 0.3V to 1.8V. Figure 5 The demonstration shows the zinc-ion battery with FeVO4 / carbon cloth material and ordinary FeVO4 as the positive electrode at 0.1A g -1 The cycling performance diagram under current density shows that the introduction of carbon cloth and more FeVO4 flower-like nanostructures effectively improves the cycling performance and stability of FeVO4 / carbon cloth material compared to the control example, indicating that it has the potential to be used as a positive electrode material for zinc-ion batteries.
[0061] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A vanadium-based electrode material, characterized in that: The invention comprises a carbon-containing substrate and FeVO4; the FeVO4 has a flower-like structure composed of thin sheets and is in-situ loaded on the carbon-containing substrate.
2. The vanadium-based electrode material according to claim 1, characterized in that: The carbon-containing substrate includes carbon cloth.
3. The method for preparing the vanadium-based electrode material according to claim 1, characterized in that: include: The carbon-containing substrate is immersed in a solution containing a soluble iron salt and a soluble vanadium salt, and after heating for reaction, the carbon-containing substrate is taken out and dried; The dried carbon-containing substrate is calcined to obtain the vanadium-based electrode material.
4. The preparation method according to claim 3, characterized in that: The soluble iron salt includes one or more of ferric chloride, ferric nitrate and ferric sulfate; the soluble vanadium salt includes one or more of ammonium metavanadate and vanadyl acetylacetonate.
5. The preparation method according to claim 3, characterized in that: The temperature of the heating reaction is 50-200°C.
6. The preparation method according to claim 3, characterized in that: The calcination temperature is 300-700°C.
7. The preparation method according to any one of claims 3 to 6, characterized in that: The method also includes pre-treating the carbon-containing substrate to be hydrophilic and remove a surface oxide layer before immersion.
8. A positive electrode sheet, characterized in that: Comprising the vanadium-based electrode material according to claim 1 or 2.
9. A battery, characterized in that: It comprises a negative electrode plate, a separator, an electrolyte, and the positive electrode plate as claimed in claim 8.
10. An electrical device, characterized in that: A battery comprising the battery of claim 9.
